Research on the interpretation of Chinese Grotto art connotation and digital protection of artificial intelligence based on national self-confidence - Li, Xiaoshu; Ji, Kang; Mohd Yusof, Mohd Johari (Engineering and Scientific Research Groups, 2024)
Chinese Buddhist grottoes are the testimony of history and the crystallization of human technology and culture as well as the physical remains of human creative activities. The neutral shape of Buddha statues reflects the aesthetic pursuit of “neutralization” in traditional Chinese culture. The solemnity and gentleness of the Buddha statues are expressed through external modelling technique and line carvings, which embodies the characteristics of “conveying the spirit with form” in China culture. This paper analyzes China Grottoes’ art from the aspects of “meaning”, “god is outside the form”, “expressing the spirit with the form”, phonology, “charm” and “expressing the spirit with the lines” through literature review, and then analyzes the awareness of digital protection, technical methods and key projects at domestic and overseas. In recent years, the digital protection of cultural relics has been continuously improved under the multi-disciplinary application of artificial intelligence, which not only enhances the influence of cultural communication, but also makes cultural relics more powerful and dynamic. Through the restoration of Buddha statues by digital simulation and the planning of restoration projects through the precise measurement given by this digital models can realize the complete digital filing and permanent preservation of important cultural relics and improve the protection and utilization of digital cultural heritage.